Evaluation of the Hepatoprotective Effects of the Flavonoid-Containing Ethyl Acetate Fraction Obtained after n-Hexane Defatting of Matoa (Pometia pinnata) Fruit Peel on a DMN-Induced Hepatic Fibrosis Model in Rats: A Histopathological and Serum Biomarker Approach - Emma Jayanti Besan; Atun Qowiyyah; Korinus Suweni; Yunita Kristina; Ziza Putri Aisyia Fauzi (CV. Get Press Indonesia, 2025)
Liver fibrosis is a progressive liver disorder and a major global health concern, prompting increasing interest in natural products with antifibrotic potential. Pometia pinnata, traditionally used to treat liver disorders, lacks sufficient experimental evidence supporting its hepatoprotective effects. This study evaluated the hepatoprotective and antifibrotic activity of a flavonoid-containing ethyl acetate fraction obtained after n-hexane defatting of Pometia pinnata fruit peel in a dimethylnitrosamine (DMN)-induced hepatic fibrosis rat model. Male rats were divided into six groups: normal control, DMN control, three treatment groups receiving the flavonoid fraction at doses of 50, 100, and 200 mg/kg body weight, and a silymarin-treated group (100 mg/kg). Dose selection was based on preliminary toxicity data and previous studies on flavonoid-rich extracts. Liver injury was assessed using serum biochemical markers (ALT, AST, ALP, and bilirubin), histopathological examination, and fibrosis scoring with Masson’s Trichrome staining. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test (p < 0.05). DMN significantly induced hepatic injury and fibrosis, while flavonoid fraction treatment improved liver function and histological features in a dose-dependent manner. The highest dose showed effects comparable to silymarin and significantly reduced fibrosis scores (r = −0.91, p < 0.001). These findings indicate that Pometia pinnata fruit peel exhibits promising hepatoprotective and antifibrotic potential.